Ética empresarial: uma leitura à luz do pragmatismo de Charles Sanders Peirce - Arruda Junior, Haroldo de (2013)
This Ph.D. Dissertation is an aftermath of our Master s Thesis defended at the Pontifical Catholic University of São Paulo, Brazil, under the tutorship of Professor Ivo Assad Ibri. In it we intend to reflect upon the character of ethicity which structures business organizations, owing to the ever-growing process of globalization and consequent cultural hybridism, encompassing not only its main beacons in the sphere of theoretical intentions, but also by examining the effective performance of these organisms within society. This double task of examination and reflection, founded upon a logic entailment between the interiority of the declarative plane and the exteriority of the sphere of actions in their facticity and historicity, is backed by heuristics of Classical Pragmatism, mainly by the one as conceived by Charles S. Peirce (1839-1914). Peirce s Pragmatism, which is a very distinct version from that of William James instrumentalism and John Dewey s utilitarism, amplifies that entailment between inner and outer worlds, an originally logic on in nature, that is, a one requiring a formal consistency between the universal and the particular, for a dimension wherein such entailment dons itself of a necessary ethicity. Under this light, a new semantic scope to the term Pragmatism will be introduced right from the start, an altogether different one, by the way, from its vulgar meaning, especially in the sphere of a rationality that seems to mean a practice, and therefore, almost naturally, as a synonym of efficiency, as is the case of a quality held as primordial in the field of business organizations in general. However, the legitimate conception of Peirce s pragmatism requires the understanding of the expression practical consequences, present in the utterance of his maxim, not only as action, as if the purpose of a concept could be reduced to its efficient cause, but as a general instance evolutionary directed toward a final cause. To introduce this theoretical tissue right at the beginning, so as to provide a logic-ethical correction, will be something that is part of this research, thus emphasizing that every action brings within itself a semiotic index of its context of virtues and values. Such context of values regards the ethical dimension of Pragmatism, more appropriately in its pragmatic sense, which establishes that commitment between the actions of a subject, a community or an organization with the sphere that intentionalizes them, and more, with the ends they aim at, thus trespassing the mere logic consistency between the theoretical and practical spheres. At play, in such objective, is the analysis of how such actions, which affect the individual and social actions, in their widest scope, can be considered ethically approvable